Effectiveness of oral famotidine in reducing the hematologic complications of radiotherapy in patients with esophageal and cardia cancers: a randomized controlled trial - Mina Rostami; Omid Yelghi; Zhaleh Karimi Moghaddam; Alireza Zeraatchi; Hamed Rezaeejam; Alireza Sadeghi (Radiation Oncology, 2023)
Abstract Background Chemoradiotherapy complications has always been of great concern to both clinicians and patients during the course of treatment. The purpose of the present study was to examine the effectiveness of oral famotidine on the reduction of hematologic complications of patients with esophageal and gastric cardia cancers undergoing radiotherapy. Methods A single-blind controlled trial was conducted on 60 patients with esophageal and cardia cancers, who were undergoing chemoradiotherapy. Patients were randomly assigned to 2 groups with 30 patients to receive either 40 mg of oral famotidine (daily and 4 h before each session) or placebo. Complete blood count with differential, platelet counts, and hemoglobin levels were obtained weekly during treatment. The main outcome variables were lymphocytopenia, granulocytopenia, thrombocytopenia, and anemia. Results The findings indicated a significant effect of famotidine on reduction of thrombocytopenia among intervention group compared to control group (P < 0.0001). Even so, the effect of intervention was not significant for other outcome variables (All, P ≥ 0.05). The lymphocyte (P = 0.007) and platelet (P = 0.004) counts were also significantly greater in famotidine group in comparison with placebo group at the end of the study. Conclusion As evidenced by the findings of the current study, famotidine might be recommended as an effective radioprotective agent among patients with esophageal and gastric cardia cancers to prevent Leukocyte and platelet reduction to some extent. Trial registration This study was prospectively registered at irct.ir (Iranian Registry of Clinical Trials) with the code IRCT20170728035349N1, 2020-08-19.